THE DYNAMICS OF MUSLIM-CHRISTIAN RELATIONS IN THE MEDIA: THE PERSPECTIVE OF DALIHAN NA TOLU AS A SOCIAL HARMONY APPROACH - Godlif Sianipar (CV. RADJA PUBLIKA, 2024)
This study analyzes the dynamics of Muslim-Christian relations in the media in Indonesia and explores the application of the Dalihan Na Tolu perspective as an approach to social harmony. Based on media content analysis, in-depth interviews, and participatory observations, it was found that the media often portrays Muslim-Christian relations through three main narratives: conflict, dialogue, and collaboration. Factors such as political orientation, economic interests, and audience preferences influence how the media frames interfaith issues. Dalihan Na Tolu's perspective, with its values of Hula-hula (respect), Dongan Tubu (equality), and Boru (service), offers a relevant local approach to strengthening harmony through inclusive and constructive narratives. These findings show that media that adopt local values in their reporting have the potential to be effective agents of change in promoting social harmony in Indonesia. This research contributes to the literature of peace journalism and emphasizes the importance of a local culture-based approach in managing interfaith relations in diverse societies.